The Effectiveness of Authentic Materials to Improve Reading Comprehension of The Eighth Grade Students of SMP Negeri 5 Palu - Nurjannah, Siti; Aminah Suriaman; Agussatriana, Agussatriana; Anjar Kusuma Dewi (Universitas Cokroaminoto Palopo, 2024)
The objective of this research was to prove whether or not the use of authentic materials improves reading comprehension of the eighth grade students of SMP Negeri 5 Palu. This research used quasi-experimental research design, involving an experimental group and a control group. The population of the research was the eighth grade students of SMP Negeri 5 Palu. The sample was taken by applying purposive sampling technique. The sample was 27 students of VIII B as control group and 27 students of VIII D as the experimental group. The instrument in collecting data was test (pretest and posttest). In this research, authentic materials is original materials in the form of printed materials, which can be found in everyday life with a clear context. The data in this research were analyzed statistically with a significance level of 0.05 and degree of freedom (df) = 52, the results showed that value is 8.47 which is greater than 2.0126, which indicated that the null hypothesis ( ) is rejected and the alternative hypothesis ) is accepted. In other words, the reading comprehension of the eighth grade students of SMP Negeri 5 Palu can be improved by using authentic materialsThe objective of this research was to prove whether or not the use of authentic materials improves reading comprehension of the eighth grade students of SMP Negeri 5 Palu. This research used quasi-experimental research design, involving an experimental group and a control group. The population of the research was the eighth grade students of SMP Negeri 5 Palu. The sample was taken by applying purposive sampling technique. The sample was 27 students of VIII B as control group and 27 students of VIII D as the experimental group. The instrument in collecting data was test (pretest and posttest). In this research, authentic materials is original materials in the form of printed materials, which can be found in everyday life with a clear context. The data in this research were analyzed statistically with a significance level of 0.05 and degree of freedom (df) = 52, the results showed that value is 8.47 which is greater than 2.0126, which indicated that the null hypothesis ( ) is rejected and the alternative hypothesis ) is accepted. In other words, the reading comprehension of the eighth grade students of SMP Negeri 5 Palu can be improved by using authentic materials